2010
DOI: 10.3109/00016480902963053
|View full text |Cite
|
Sign up to set email alerts
|

Local delivery of reporter gene to the cochlea does not spread to brain tissue in an animal model

Abstract: The patterns of the fluorescent signals with red and green filters were compared to identify the GFP signals in the brain tissue. GFP reporter gene expression was not detected in any examined brain region in any of the animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…One group transduced immature cochlear cells in utero, showing transgene expression and hearing impairment (Bedrosian et al 2006), but did not explore the capacity to transduce postnatal OC cells. Three additional reports did not find evidence of OC transduction after perilymph injection (Han et al 1999;Pietola et al 2008;Duan and Mi 2010). Han et al (1999) also used LV in postnatal cochlear explants but with a lower dose and different administration showing low rate of transduction in the OC and no HC transduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One group transduced immature cochlear cells in utero, showing transgene expression and hearing impairment (Bedrosian et al 2006), but did not explore the capacity to transduce postnatal OC cells. Three additional reports did not find evidence of OC transduction after perilymph injection (Han et al 1999;Pietola et al 2008;Duan and Mi 2010). Han et al (1999) also used LV in postnatal cochlear explants but with a lower dose and different administration showing low rate of transduction in the OC and no HC transduction.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these vectors have not been successful in transducing the postnatal OC. Studies reported poor results, with lack of transduction of HC in vitro and lack of reaching the OC in vivo (Han et al 1999;Pietola et al 2008;Duan and Mi 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro infection of cochlear explants from neonatal rats allowed successful transduction of SGNs and some supporting cells, but not of hair cells (145). One report demonstrated that lentivirus injected into the rat scala tympani remained within the cochlea, with no evidence of its spread to the central nervous system; this is an important feature with regards to minimizing toxicity to tissues outside the cochlea and provides further support for the safety of innerear, viral-mediated gene delivery (95).…”
Section: Viral Vectorsmentioning
confidence: 99%
“…For example, how effective and specific are various viruses, including adenovirus, lentivirus, and many subtypes of AAVs, in infecting the mature organ of Corti? Many studies showed inconsistent transduced cell groups and varied transduction efficiency (Akil et al, 2012; Duan et al, 2010; Han et al, 1999; Kho et al, 2000; Kilpatrick et al, 2011; Konishi et al, 2008; Liu et al, 2005; Luebke et al, 2001; Mondain et al, 1998; Stone et al, 2005), resulting from different ex vivo or in vivo conditions, different animal models, different expressing vectors, different viral diffusion rates, etc. Moreover, will the virus affect other cells and cause permanent genetic changes?…”
Section: Clinical Applicationsmentioning
confidence: 99%